2023
DOI: 10.3390/plants12061246
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical Practices and Management for Commercial Cultivation of Portulaca oleracea as a Crop: A Review

Abstract: Soil is an essential resource, and its degradation is challenging modern agriculture, while its impact is expected to increase in the near future. One of the strategies to address this issue is to incorporate new alternative crops able to tolerate arduous conditions, as well as for the use of sustainable agricultural practices in order to recover and/or improve soil health. Additionally, the increasing market for new functional/healthy natural foods promotes the search for potential alternative crop species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 124 publications
(198 reference statements)
0
5
0
Order By: Relevance
“…Invasive weeds often have a high degree of adaptability to a wide range of climatic conditions, enabling them to thrive in diverse habitats (Paudel & Battaglia, 2021; Hierro et al ., 2022). The common purslane ( Portulaca oleracea ), for example, thrives in both moist and dry environments due to its succulent leaves and ability to tolerate drought (Wang et al ., 2020; Carrascosa et al ., 2023). They may also show rapid growth, early maturity, or more efficient resource use (Gann et al ., 2019).…”
Section: General Concept Of Invasivenessmentioning
confidence: 99%
“…Invasive weeds often have a high degree of adaptability to a wide range of climatic conditions, enabling them to thrive in diverse habitats (Paudel & Battaglia, 2021; Hierro et al ., 2022). The common purslane ( Portulaca oleracea ), for example, thrives in both moist and dry environments due to its succulent leaves and ability to tolerate drought (Wang et al ., 2020; Carrascosa et al ., 2023). They may also show rapid growth, early maturity, or more efficient resource use (Gann et al ., 2019).…”
Section: General Concept Of Invasivenessmentioning
confidence: 99%
“…Portulaca oleracea L. (known as purslane) is an annual succulent dicot plant, belonging to the family Portulaceceae Juss [ 1 ]. It grows mainly in the tropics and subtropics [ 1 ] but it is consumed worldwide [ 2 ]. It is an important plant because of its nutritional value [ 3 , 4 ] and medicinal benefits [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The function of P. oleracea L. recorded in the Compendium of Materia Medica (本草纲目) includes clearing heat and removing toxicity, anti‐dysentery, cooling blood for hemostasis and anti‐consumptive thirst. Besides, P. oleracea also provides nutritional benefits due to its rich omega‐3 fatty acids and antioxidant properties 7 …”
Section: Introductionmentioning
confidence: 99%
“…Besides, P. oleracea also provides nutritional benefits due to its rich omega-3 fatty acids and antioxidant properties. 7 Modern pharmacological studies have shown that P. oleracea possesses a variety of bioactivities, including antibacterial, 8 antiulcerogenic, anti-inflammatory, 9 antioxidant, 10 neuroprotective, 11 antidiabetic, 12 antioxidant, 13 anticancer, 14 antimicrobial, 15 antiinflammatory, 16,17 antiulcerogenic, 18 hepatoprotective activity, 19 and wound-healing 20 properties. Besides, there are many compounds, including flavonoids, alkaloids, fatty acids, terpenoids, polysaccharides, vitamins, sterols, proteins and minerals, that have been isolated from P. oleracea.…”
Section: Introductionmentioning
confidence: 99%